Fast relaxing red and near-IR switchable azobenzenes with chalcogen and halogen substituents: periodic trends, tuneable thermal half-lives and chalcogen bonding - Kerckhoffs, A; Christensen, K; Langton, MJ (Royal Society of Chemistry, 2022)
Molecular photoswitches operating in the red to near-IR region with controllable thermal relaxation rates are attractive components for photo-regulating biological processes. Herein, we report the synthesis of red-shifted azobenzenes functionalised with the heavier chalcogens and halogens that meet these requirements for biological application; namely fatigue-resistant photo-switching with red and near IR light and functional handles for further functionalisation for application. We report robust periodic trends for the chalcogen and halogen azobenzene series, and exploit intramolecular chalcogen bonding to tune and redshift the absorption maxima, supported by photo-physical measurements and solid-state structural analysis. Remarkably, the rate of the Z → E thermal isomerisation can be tuned over timescales spanning 107 s by judicious choice of chalcogen and halogen substituents.